Video research in disciplinary literacies - Ortlieb, Evan.; Shanahan, Lynn E.; McVee, Mary B. (Bingley, U.K. : Emerald, 2015)
This edited volume provides a collection of research-based chapters that reflect the state of the art for video reflection in literacy settings. The volume foregrounds explorations of disciplinary literacies and discourses in teacher education and pre-K-12 classrooms. Authors explore literacy and use of video in relation to English Language Arts, math, science, social studies, and educational administration across a variety of contexts ranging from a preschool classroom, to a high school, to preservice and inservice teacher education and development. In their research-based studies, authors address topics of disciplinary literacy, identity, discourses or multimodality. Some chapters present research findings while others are specifically devoted to methodological concerns and addresses how researchers who wish to carry out literacy investigations using video can work through challenges in research, design, or analysis.
See it, try it, and reflect on it (STAR): using video to scaffold and support preservice teachers in the reflective process of developing participation questioning discourse / J. Matt Switzer, Dawn Teuscher, Daniel Siebert -- The role of video in a literacy collaboration to re-engage struggling students / Christopher W. Johnson, Burke Scarbrough -- Growing in the disciplinary literacy of writing: videotaped peer talk and reflection in a sixth-grade classroom / Karen Kreider Yoder -- Affordances of digital video editing among prospective English and science teachers / David Bruce, Randy Yerrick, Michael Radosta, Chris Shively -- Exploring the use of video coding in literacy and English teacher preparation / Seth A. Parsons, Audra K. Parker, Kristien Zenkov, Christine Degregory, Laurel Taylor, Daniel Kye, Summer Haury -- How do I know what I think until I see what I produce in my video?: a case for video reflection / Bridget Dalton, Blaine E. Smith -- The dialogic construction of a teaching vision: preservice teachers imagine their practice through digital storytelling / Jackie Sydnor, Linda Coggin, Tammi Davis, Sharon Daley -- What beginning teachers narratives about video-based instruction tell us about learning to teach science and literacy / Mark W. Conley, Hosun Kang -- "what were you thinking?" bilingual preschool students talk about reading practices through video reflection / Joseph C. Rumenapp, Colleen E. Whittingham, Emily Brown Hoffman -- Using video, multimodal interaction analysis, and dramaturgical metaphors to understand disciplinary literacies and educational leadership / Dru Tomlin -- Preservice teachers use digital video to reflect on their own literacy learning / Douglas Kaufman -- Using expansive learning as a model for video reflection in teacher education / Roy Rozario, Evan Ortlieb -- Genre as a potential scaffold for preservice teachers reflection on their videotaped lessons / Angelina N. Kuleshova, Alysia D. Roehrig.
Includes bibliographical references.
Print version record
Keywords: Education -- General; Education; Visual education; Literacy